Analysis of speech and language alterations in diabetics affected by COVID-19 (Research, Society and Development, 2022)
Purpose: To compare the speech therapy changes in diabetic and non-diabetic users, hospitalized with COVID 19. Methods: This is a case-control, observational and retrospective study carried out through the analysis of medical records of users infected with COVID-19 hospitalized at General Hospital of Goiânia, with and without a diagnosis of diabetes, in the biennium 2020-2021. Results: A total of 100 individuals infected with COVID-19 participated in the study. In this sample, the prevalence of individuals without diabetes was observed. This sample consists mostly of male individuals and the mean age observed was 54.4 ± 13.7 years. In this study, sleepiness was a prevalent condition in diabetic patients. This finding may be the result of several factors, in particular, the metabolic changes associated with viral infection. Conclusion: There were no significant speech-language disorders in diabetic patients with COVID-19. However, we observed that the prevalence of alterations in the alertness level was higher in this group, and that they can impact the decision-making in speech-language pathology conducts.